Estimating the Concentrations of Natural Isotopes of 238 U and 232Th and Radiation Dose Rates for Wasit Province-Iraq by Gr-460 system - ZARKOOSHİ, Ahmed and LATIF, Kamal Hussein and HAWI, Fadhil (International Journal of Computational and Experimental Science and Engineering, 2021)
This paper includes the measurement of the concentrations of natural radioactive isotopes of 238U, 232Th, and radiation dose rates for selected areas of Wasit province.GR-460 system has been used for the radiological survey operations, it is a portable system, installed inside a minibus and inside the system, there is a Sodium Iodide Detector (NaI), that has the ability to measure the concentrations of natural radioactive isotopes in (ppm) unit and measure the radiation dose rates in µR/h unit. The measurement results showed the absence of any significant increase in the 238U and 232Th concentration where the concentration of isotopes 238U and 232Th, were 3.35 and 5.46 ppm respectively, it is authorized and acceptable. The values of radiation dose rates ranged between 45-65 ոSv/հ, and all these values are within the natural radiation background. Eleven radioactive sources type 226Ra have been detected beside destroyed industrial facility because of the war 2003 they had been used in the lightning arresters technology in the last regime. These sources treated and placed in armored containers and taken to the Iraqi main store (Iraqi Organization of Atomic Energy Site), the radiation dose measurements ranged between 72- 48 µR/h, which is higher than the natural radiation background.